Embodied cultural property: Contemporary and traditional dance practices. Issue 2 (May 2022) - Whatley, Sarah
Abstract: This article discusses the implications of recording and digitizing a variety of cultural and contemporary dance performance practices, core to a European project known as WhoLoDancE, which focused on issues of reuse, ownership, property, and responsibility. The recordings and subsequent processing of dance material into digital data raised questions about the responsibilities to the dancers who have contributed their material to the project, particularly when it is transformed into data visualizations that can be accessed and reused by others. The article not only focuses on how value accrues in these kinds of resources and sometimes in unexpected ways but also draws attention to how dance remains bound to the communities in which it is performed and tends to resist its abstraction from the body to be commodified as a form of cultural property. This then points to how dance, as intangible cultural heritage, is self-regulating in terms of principles of ownership and attribution.